Letter (scrapped draft) - Citrine, Walter, 1887-1983
1941-03-13 013-0048-002 International. WMC/WJB/DT/780. 13th March, 1941. Mr. J. Lane, Dartford Trades Council and Labour Party, 205, Station Road Dartford Heath, Dartford, KENT scrapped Dear Mr. Lane, Spanish Trade Unionists. In reply to your letter of the 12th instant relating to the Spanish Government's persecution of trade unionists, we may say that we have approached our own Foreign Office on several occasions about this matter. We have also made representations with regard to our colleage Caballero, and were assured that everything would be done that was possible in order to induce the Spanish Authorities to spare his life and give him his freedom. Yours sincerely, General Secretary. 292/946/13/48(ii)